1987
DOI: 10.1056/nejm198707093170201
|View full text |Cite
|
Sign up to set email alerts
|

Familial Occurrence of Accessory Atrioventricular Pathways (Preexcitation Syndrome)

Abstract: Accessory atrioventricular pathways, the anatomical structures responsible for the preexcitation syndromes, may result from a developmental failure to eradicate the remnants of the atrioventricular connections present during cardiogenesis. To study whether preexcitation syndromes could also be transmitted genetically, we determined the prevalence of preexcitation in the first-degree relatives of 383 of 456 consecutive patients (84 percent) with electrophysiologically proved accessory pathways. We compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
2
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(75 citation statements)
references
References 11 publications
0
70
2
3
Order By: Relevance
“…Wolff-Parkinson-White syndrome (WPW)' is one of the most common congenital cardiac abnormalities with a prevalence of 0.15-3 per 1,000 (1). WPW results from an anomalous atrioventricular (AV) conduction pathway that can produce ventricular preexcitation and paroxysmal reentrant tachycardias.…”
Section: Introductionmentioning
confidence: 99%
“…Wolff-Parkinson-White syndrome (WPW)' is one of the most common congenital cardiac abnormalities with a prevalence of 0.15-3 per 1,000 (1). WPW results from an anomalous atrioventricular (AV) conduction pathway that can produce ventricular preexcitation and paroxysmal reentrant tachycardias.…”
Section: Introductionmentioning
confidence: 99%
“…The nonhydropic male infant weighed 4150 g and demonstrated minimal signs of neonatal distress (Apgar score 5 and 1 at 1 and 5 min respectively) with delayed onset of respiration and bradycardia, although the pH of umbilical cord blood was normal (art: 7.32, ven: 7.39). Postpartum echocardiography confirmed normal heart anatomy and ECG showed pre-exitation with delta-waves [14], but no signs of digitalis intoxication. Thus a Wolff-Parkinson-White syndrome was diagnosed and continuation of digoxin treatment was indicated [6,12].…”
Section: Clinical Information and Resultsmentioning
confidence: 76%
“…8 The results showed that the prevalence of manifest AP in first-degree relatives was significantly higher than that of the general population (0.55% vs 0.15%). Also, they examined the pedigrees of patients with first-degree relatives with AP and proposed autosomal dominance as a mode of transmission of familial WPW syndrome.…”
Section: Discussionmentioning
confidence: 84%
“…Compared with sporadic WPW syndrome, familial WPW syndrome is characterized by a high incidence of multiple pathways, lack of male dominance, high risk of sudden death, and low association of structural heart disease. 8 Concealed APs that conduct impulse only in the retrograde direction can also be an anatomic substrate for AVRT. However, the existence of a concealed AP cannot be suspected until the EPS-confirmed PSVT develops.…”
Section: Discussionmentioning
confidence: 99%